2010
DOI: 10.1007/s11999-009-1020-6
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Complications From Enoxaparin Treatment After Arthroplasty

Abstract: Pulmonary embolism (PE) complicates 1% to 10% of total joint arthroplasties and generally requires immediate anticoagulation. Low-molecular-weight heparins have supplanted unfractionated heparin as the treatment of choice for PE and hold a 1A recommendation from the American College of Chest Physicians for this indication. However, the complications of enoxaparin treatment begun in close proximity to arthroplasty surgery are not well described. We examined the records of 135 patients who underwent total joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…These data are compatible with the reports of multiple authors [13][14][15] who have cautioned against instituting therapeutic anticoagulation in the first postoperative week given the high rate of bleeding complications, longer hospitalizations, and higher transfusion requirements. The treatments were varied but similar for small and large clots.…”
Section: Discussionsupporting
confidence: 90%
“…These data are compatible with the reports of multiple authors [13][14][15] who have cautioned against instituting therapeutic anticoagulation in the first postoperative week given the high rate of bleeding complications, longer hospitalizations, and higher transfusion requirements. The treatments were varied but similar for small and large clots.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical site bleeding increases the risk of neurologic damage, infection, reoperation, and delays recovery [5,7,14,17,25,26]. Neviaser et al found that postoperative therapeutic enoxaparin treatment had a 10% rate of major and a 27% rate of minor bleeding complications in TJA patients [21]. Our study demonstrates that the diagnosis of PE was associated with increased risks of hematoma/seroma, postoperative infection, gastrointestinal bleed, and thrombocytopenia compared with patients who did not have this diagnosis.…”
Section: Discussionmentioning
confidence: 58%
“…Although the risk of VTE is decreased with thromboprophylaxis, it is not completely eliminated . Additionally, the pharmacological agents commonly employed for VTE prophylaxis carry a risk of bleeding, which can introduce a significant source of postoperative morbidity …”
Section: Discussionmentioning
confidence: 99%
“…VTE prophylaxis includes anticoagulants, mechanical devices and early ambulation . The armamentarium of pharmacological agents available to prevent VTE is broad but mostly limited to medications that substantially increase the risk of surgical site and/or gastrointestinal bleeding, such as low molecular weight heparin (LMWH), subcutaneous heparin (SQH), warfarin and aspirin (ASA) …”
mentioning
confidence: 99%